Effects of Different Fertility Rates on Chick Quality and Hatching Parameters in Hatching Eggs - İsmail Durmuş; Serdar Kamanlı; Yeliz Kaşko Arıcı; Mehmet Akif Özcan (Turkish Journal of Agriculture: Food Science and Technology, 2014)
This study was conducted to investigate the hatching parameters differences between the hatching eggs which were controlled or not for fertility at 18th day of embryo development in the hatchery unit. Hatching was conducted with hatching eggs of Atak-S commercial layers parent stocks. Four treatment groups were constituted; 1) 95% fertility, fertility control at 18th day, 2) 95% fertility, no fertility control at 18th day, 3) 75% fertility, no fertility control at 18th day and 4) 50% fertility, no fertility control at 18th day. There were no significant differences between the groups in terms of fertility rate, hatching efficiency hatchability of fertile eggs and early-, middle and late period embryo mortality. Chick quality according to Pasgar score chick quality assessment differed significantly between the treatment groups. The results of the present study indicate that transferring of eggs to the hatcher without fertility control at 18th day of embryo development did not affect the hatching results, but chick quality decreased when the fertility rate decreased below 45%.